2013
DOI: 10.1136/bcr-2013-200755
|View full text |Cite
|
Sign up to set email alerts
|

Multiple tendon xanthomas in patient with heterozygous familial hypercholesterolaemia: sonographic and MRI findings

Abstract: Tendon xanthomas are a component of familial hypercholesterolaemia, which is a hereditary disease and characterised by elevated low-density lipo protein cholesterol plasma levels and premature coronary artery disease. Tendon xanthomas are diagnostic for heterozygous familial hypercholesterolaemia (HFH) and they mostly occur in Achilles tendon. Sonography and MRI are superior to clinical assessment and are useful in detecting tendon xanthomas. In this report, we present ultrasonographic and MRI findings of mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
0
11
0
2
Order By: Relevance
“…Studies have shown that the most frequent site for xanthomas in these patients is the Achilles tendon . Other sites can include the extensor tendons of the hands and feet, as the extensor tendon areas are subject to mechanical stress …”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown that the most frequent site for xanthomas in these patients is the Achilles tendon . Other sites can include the extensor tendons of the hands and feet, as the extensor tendon areas are subject to mechanical stress …”
Section: Discussionmentioning
confidence: 98%
“…Xanthomas have been indicated to commonly occur in patients with FH (1). A previous study has shown that the most frequent site for xanthomas is the Achilles tendon (11). Other frequent sites include the extensor tendons of the hands and feet, as the extensor tendon areas are subject to mechanical stress (11).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that the most frequent site for xanthomas is the Achilles tendon (11). Other frequent sites include the extensor tendons of the hands and feet, as the extensor tendon areas are subject to mechanical stress (11). The mechanical stress encountered in tendons is similar to recurrent trauma, which is thought to predispose these sites to the development of xanthomas (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,7] A previous study has shown that the most frequent site for xanthomas is the Achilles' tendon. [8] Xanthomas consist of cholesterol, cholesterol esters, triglycerides, phospholipids and numerous lipid-laden foamy macrophages. [9] case, the patient had lesions at similar sites.…”
Section: Discussionmentioning
confidence: 99%